Genadendal and its satellites : a history of the Moravian Mission stations at the Cape, 1737-1869 - Krüger, Bernhard (Rhodes University, Faculty of Divinity, Department of Divinity, 1966)
J,F.w. Kühn, a member of the Moravian Mission Board, wrote in 1871 to the Superintendent at Genadendal that the closed settlements in South Africa were a precious and unique feature of mission work for which the brethren should be grateful. While he had been at the Gape, he had suffered under the difficulties of their management, but from the distance, and in comparison with mission work elsewhere, he had learnt to appreciate them as a great blessing. The questions arise: How dld they originate, develop and survive for so long? What were their characteristics, advantages and limitations? What factors contributed to their development? How did they fit into their milieu and influence it? The following thesis is an effort to give a detailed history of their development and an appraisal. I have endeavoured to give a vivid picture of personalities and events within the limits of historical correctness, because I consider it the noblest aim of historical research to confront us with the past in such a way that personal understanding becomes possible. In as much as we meet those who have made history. or have been part of it, in person, we can arrive at a deeper appreciation of their achievements, problems and failures.
Keywords: Moravians -- Missions -- South Africa -- Genadendal; Missions -- South Africa -- History; Genadendal (South Africa) -- History; Cape of Good Hope (South Africa) -- History -- To 1795; Cape of Good Hope (South Africa) -- History -- 1795-1872